Too Much of a Good Thing: Investigating the Association between Actual Smartphone Use and Individual Well-Being - David, Meredith E.; Roberts, James A.; Christenson, Brett (International journal of human-computer interaction, 2018)
Research suggests that people around the world spend anywhere from an hour to as much as ten hours daily on their smartphones. However, the vast majority of this research has used self-reported data, which is widely considered unreliable. The present research is among the first to capture actual smartphone use and to examine its relationship with individual and relational well-being. Results reveal that, although smartphone use is generally negatively associated with well-being, this is not always so. Deeper analyses show that certain categories of apps are positively associated with well-being, thus revealing a more nuanced relationship between smartphone use and individual well-being. Research which suggests a negative association between smartphone use and well-being may represent an oversimplified perspective of a complex relationship.